2019
DOI: 10.1038/s41574-019-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the key characteristics of endocrine-disrupting chemicals as a basis for hazard identification

Abstract: Endocrine-disrupting chemicals (EDCs) are exogenous chemicals that interfere with hormone action, thereby increasing the risk of adverse health outcomes, including cancer, reproductive impairment, cognitive deficits and obesity. A complex literature of mechanistic studies provides evidence on the hazards of EDC exposure, yet there is no widely accepted systematic method to integrate these data to help identify EDC hazards. Inspired by work to improve hazard identification of carcinogens using key characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
312
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(348 citation statements)
references
References 146 publications
4
312
0
4
Order By: Relevance
“…This study has demonstrated the decrease in the testosterone level only after higher doses (100 and 200 mg/kg/day), in accordance with the results in our study [81]. Other studies have shown that BPA inhibits steroidogenesis in the rat testis and reduces testosterone secretion, thus inhibiting the activity of GnRH neurons, and lowering the expression of steroidogenic enzymes [13,82]. Jin et al (2013) concluded that BPA orally administrated to the rats resulted in an impairment of spermatogenesis caused by stopping germ cells meiosis process and thus activating the apoptosis pathway in germ cells [83].…”
Section: Antiandrogen Activity and Serum Testosterone Levelsupporting
confidence: 93%
See 1 more Smart Citation
“…This study has demonstrated the decrease in the testosterone level only after higher doses (100 and 200 mg/kg/day), in accordance with the results in our study [81]. Other studies have shown that BPA inhibits steroidogenesis in the rat testis and reduces testosterone secretion, thus inhibiting the activity of GnRH neurons, and lowering the expression of steroidogenic enzymes [13,82]. Jin et al (2013) concluded that BPA orally administrated to the rats resulted in an impairment of spermatogenesis caused by stopping germ cells meiosis process and thus activating the apoptosis pathway in germ cells [83].…”
Section: Antiandrogen Activity and Serum Testosterone Levelsupporting
confidence: 93%
“…This definition of EDCs was later endorsed by the Scientific Committee of the European Food Safety Authority [12]. Recent Expert Consensus Statement developed ten key characteristics that can be used to identify, organize, and utilize mechanistic data during EDCs evaluation [13]. However, there are some areas in which there is still a lack of scientific consensus, such as the existence of thresholds for EDCs, non-monotonic dose responses (NMDR), and critical windows of exposure, as recently stated in the report of Endocrine Disrupters Expert Advisory Group [14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the EPA completed a "Framework for Incorporating Human Epidemiologic & Incident Data in Risk Assessments for Pesticides" which noted that toxicology and risk assessment are undergoing transformational changes driven by new research [111]. One such development relevant to risk assessment is the identification of Key Characteristics applicable to endocrine disruption [112], male and female reproductive toxicity [113,114] and carcinogenesis [115,116]. The Key Characteristics approach highlighted the diversity of toxicity pathways that can lead from exposure to environmental contaminants to an elevated risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 The conclusions of a third group at the March 2018 meeting, which focused on endocrine disruption, were published in Nature Reviews Endocrinology in November 2019. 10 Experts also met in September 2019 to identify key characteristics for neurotoxicity and developmental neurotoxicity, while meetings to discuss cardiotoxicants and toxic bioactive chemicals are planned for later in 2020.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%